Audit of paediatric cardiac services in South Africa - Hoosen, E.G.M.; Cilliers, A.M.; Hugo-Hamman, C.T.; Brown, S.C.; Harrisberg, J.R.; Takawira, F.F.; Govendrageloo, K.; Lawrenson, J.; Hewitson, J. (SA Heart Journal, 2017)
Objective: To evaluate paediatric cardiac services in South Africa with respect to referral base, services provided and human resources. Study design: A descriptive study design was used. An audit of the referral base, personnel and activity of paediatric cardiac units throughout South Africa was conducted by means of a questionnaire. A specialist from each centre was asked to provide the relevant data. Where accurate data was not available, estimates were provided by practitioners within each centre. Results: All identified units participated in the audit. Three were private sector units while the other five were primarily public sector units. Twenty four paediatric cardiologists, equally distributed between public and private sector units, were practicing in the country as at end 2008, with a further eight paediatricians undergoing training in paediatric cardiology. This is significantly less than the 88 paediatric cardiologists required for the population of South Africa. Eight paediatric cardiac surgeons were operating predominantly on children in public hospitals and five in private institutions. An estimated 1370 operations for congenital heart disease were performed over a one year period, with 800 of these in the public sector. Extrapolating from accepted estimates of congenital heart disease incidence, this represents conservatively, less that 40% of operations required for the population. Additionally, only 26% of the estimated 114 simple transposition of great arteries born annually were operated on, indicating serious deficiencies in the ability to adequately detect and intervene in serious congenital heart disease presenting in the neonatal period. Conclusion: The infrastructure and resources to detect and manage heart disease in children in South Africa, particularly within the public sector, are grossly inadequate.